Higher Coronary Plaque Burden in Psoriatic Arthritis Is Independent of Metabolic Syndrome and Associated With Underlying Disease Severity. Issue 3 (6th February 2018) - Szentpetery, Agnes; Healy, Gerard M.; Brady, Darragh; Haroon, Muhammad; Gallagher, Phil; Redmond, Ciaran E.; Fleming, Hannah; Duignan, John; Dodd, Jonathan D.; FitzGerald, Oliver
Abstract : Objective: To examine the effect of metabolic syndrome and psoriatic disease–related variables on coronary plaque burden in psoriatic arthritis (PsA) patients. Methods: Fifty PsA patients without symptoms of coronary artery disease (CAD) (25 with metabolic syndrome and 25 without metabolic syndrome) and 50 age‐ and sex‐matched controls underwent 64‐slice coronary computed tomography angiography. Plaque localization, segment involvement score (SIS), segment stenosis score (SSS), and total plaque volume (TPV) were calculated. Plaques were classified as calcified, mixed, or noncalcified. Kruskal‐Wallis test, rank correlations, and linear regression analyses were used to study the relationship between PsA, metabolic syndrome, and plaque burden. Results: Plaques were found in 76% of PsA patients versus 44% of controls ( P = 0.001), and a higher proportion of patients with PsA had affected coronary vessels ( P = 0.007). SIS, SSS, and TPV were greater in PsA patients than controls ( P = 0.003, P = 0.001, and P ≤ 0.001, respectively). More PsA patients had mixed plaques, and mixed plaque volume was higher than in controls ( P < 0.001). PsA patients with metabolic syndrome and those without metabolic syndrome had similar plaque burdens and types. SIS, SSS, and TPV did not show significant relationships with features of metabolic syndrome, but did significantly correlate with disease activity measures. TPV was associated with a diagnosis of PsA (B = 0.865, P = 0.008), but not with metabolic syndrome. Age, highest C‐reactive protein level, highest swollen joint count, disease duration, and plasma glucose level were independent predictors of higher plaque burden in PsA. Conclusion: PsA is associated with accelerated coronary plaque formation, particularly mixed plaques, independent of metabolic disease. Psoriatic disease activity and severity may predict coronary plaque burden better than traditional risk factors.